Integrating Mendelian randomization and multi-transcriptomic analyses to unveil the genetic association risk of regulatory T cell-mediated free cholesterol and gastric cancer - Fanyu Peng; Haitao Liu; Yesong Guo; Jing Wen; Yizhi Ge; Yanhong Luo (Discover Oncology)
Abstract Background Evidence from observational studies suggests an association between free cholesterol and gastric cancer. Immune cells play a crucial role in the tumor microenvironment of gastric cancer, and free cholesterol can influence immune cells in various ways, thereby impacting gastric cancer. The mechanisms by which free cholesterol regulates and activates the immune response to exert antitumor effects, as well as the causal relationship between free cholesterol and gastric cancer, remain unclear. Methods We employed a two-sample Mendelian randomization (MR) approach to investigate the causal relationship between 233 metabolites and gastric cancer. Additionally, we validated our findings using data from GWAS databases of similar traits. Using publicly available genetic data, we analyzed the causal relationship between 731 types of immune cells and gastric cancer. Furthermore, we explored the mediating role of regulatory T cells in the causal relationship between free cholesterol and gastric cancer through multivariable Mendelian randomization. Finally, we validated our results using data from the TCGA database and single-cell sequencing data. Findings We found a causal relationship between free cholesterol levels and gastric cancer (odds ratio [OR] = 0.89, confidence interval [CI] = 0.81–0.98, P < 0.05). We also observed a causal relationship between free cholesterol levels and regulatory T cells (odds ratio [OR] = 0.86, confidence interval [CI] = 0.75–0.98, P < 0.05), and between regulatory T cells and gastric cancer (odds ratio [OR] = 1.04, confidence interval [CI] = 1.01–1.07, P < 0.05). Additionally, our multivariable Mendelian randomization analysis indicated that regulatory T cells mediate the causal relationship between free cholesterol levels and gastric cancer. Furthermore, through single-cell sequencing analysis and data analysis from the TCGA database, we found that the expression of the free cholesterol uptake protein LDLR is negatively correlated with Treg infiltration, which further influences the occurrence and development of gastric cancer. Interpretation Our analysis indicates a causal relationship between free cholesterol levels and gastric cancer, with regulatory T cells acting as mediators. Modulating free cholesterol levels to influence regulatory T cells may offer new insights and prospects for the prevention and treatment of gastric cancer.